2013
DOI: 10.3748/wjg.v19.i38.6505
|View full text |Cite
|
Sign up to set email alerts
|

Plastic tube-assisted gastroscopic removal of embedded esophageal metal stents: A case report

Abstract: A patient with stent embedding after placement of an esophageal stent for an esophagobronchial fistula was treated with an ST-E plastic tube inserted into the esophagus to the upper end of the stent using gastroscopy. The gastroscope was guided into the esophagus through the ST-E tube, and an alligator forceps was inserted into the esophagus through the ST-E tube alongside the gastroscope. Under gastroscopy, the stent wire was grasped with the forceps and pulled into the ST-E tube. When resistance was met duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Use of PCSEMS in the treatment of benign diseases is controversial due to the adverse events described during their removal [3,9,17,21,[26][27][28][29][30]. These adverse events may include: hemorrhage, granulation or hyperplasic tissue ingrowth, obstruction, stent fracture, penetration, perforation, avulsion, fistula formation (i.e., tracheoesophageal, esophagoaortic, pericardioesophageal), and epidural abscess formation [1,3,11,17,19,28,[31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of PCSEMS in the treatment of benign diseases is controversial due to the adverse events described during their removal [3,9,17,21,[26][27][28][29][30]. These adverse events may include: hemorrhage, granulation or hyperplasic tissue ingrowth, obstruction, stent fracture, penetration, perforation, avulsion, fistula formation (i.e., tracheoesophageal, esophagoaortic, pericardioesophageal), and epidural abscess formation [1,3,11,17,19,28,[31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Short-and long-term data regarding techniques for removal of embedded stents are extremely limited. The OT procedure effectively dislodges the stent in a single procedure, although it potentially increases the risk of bleeding, perforation, and esophageal avulsion.…”
mentioning
confidence: 99%
“…Different methods for endoscopic removal of an embedded PCSEMS have been described [100][101][102][103][104][105][106]. Most studies have reported on the use of the stent-in-stent technique, which relies on the placement of an additional FCSEMS fully overlapping the location of the embedded PCSEMS.…”
Section: Factors Predicting Successful Treatmentmentioning
confidence: 99%